2007
DOI: 10.1158/1535-7163.mct-06-0665
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of glycogen synthase kinase-3β, a downstream target of the raf-1 pathway, is associated with growth suppression in medullary thyroid cancer cells

Abstract: Glycogen synthase kinase-3B (GSK-3B) is an important regulator of cell proliferation and survival. Conflicting observations have been reported regarding the regulation of GSK-3B and extracellular signal -regulated kinase (ERK1/2) in cancer cells. In this study, we found that raf-1 activation in human medullary thyroid cancer cells, TT cells, resulted in phosphorylation of GSK-3B. Inactivation of GSK-3B in TT cells with well-known GSK-3B inhibitors such as lithium chloride (LiCl) and SB216763 is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
109
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 37 publications
11
109
0
Order By: Relevance
“…Here, we show that inhibition of GSK-3 suppresses proliferation and survival of renal cancer cells. Our data are in agreement with other studies showing that inhibition of GSK-3 results in decreased proliferation and/or survival of CLL (Ougolkov et al, 2007), pancreatic , colorectal (Shakoori et al, 2005), ovarian (Cao et al, 2006), thyroid (Kunnimalaiyaan et al, 2007) and brain (Kotliarova et al, 2008) cancer cells. We also observed retardation of tumour growth by GSK-3 pharmacological inhibition in mice xenograft model using RCC cell lines (manuscript in preparation).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we show that inhibition of GSK-3 suppresses proliferation and survival of renal cancer cells. Our data are in agreement with other studies showing that inhibition of GSK-3 results in decreased proliferation and/or survival of CLL (Ougolkov et al, 2007), pancreatic , colorectal (Shakoori et al, 2005), ovarian (Cao et al, 2006), thyroid (Kunnimalaiyaan et al, 2007) and brain (Kotliarova et al, 2008) cancer cells. We also observed retardation of tumour growth by GSK-3 pharmacological inhibition in mice xenograft model using RCC cell lines (manuscript in preparation).…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies show that GSK-3b has an important function in pathogenesis of human cancer, including leukaemia (Ougolkov et al, 2007;Wang et al, 2008), pancreatic (Ougolkov et al, , 2006, prostate (Mazor et al, 2004;Sun et al, 2007), colorectal (Shakoori et al, 2005), ovarian (Cao et al, 2006), thyroid (Kunnimalaiyaan et al, 2007) and brain (Kotliarova et al, 2008) carcinomas. However, the role of GSK-3b in kidney cancer remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…So far GSK3B has been described to be involved in modulating biological processes as opposite as proliferation or apoptosis, depending on the cellular, molecular, and developmental context (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In fact, GSK3B is known to play an antiproliferative role by promoting APC-dependent phosphorylation-and hence proteosome-mediated degradation-of b-catenin, a transcription factor positively regulating Myc and cyclin D1 expression (14).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis showed that treatment with NVP-BEZ235 caused a sharp reduction in cyclin D1 protein levels in both the NCI-H720 and NCI-H727 cells, while everolimus reduced cyclin D1 protein levels in both the NCI-H720 and NCI-H727 cells to a smaller extent. It has been demonstrated previously that GSK3b activation promotes cyclin D1 degradation (Kunnimalaiyaan et al 2007). Figure 4C shows that both NVP-BEZ235 and everolimus are capable of reducing the phosphorylation levels of GSK3b at Ser 9 in both the NCI-H720 and NCI-H727 cells, indicating an increase in kinase activity of the enzyme (Martin et al 2005).…”
Section: Mtor Expression In Human Bc Cell Linesmentioning
confidence: 91%